A Review of the Impact of Artificial Intelligence on Traditional Accounting Practices and Financial Reporting - Abdullahi Ya'u Usman; Sulaiman Taiwo Hassan; Abalaka James Nda; Yusuf Adeyanju Yisau (International Journal of Science and Society (IJSS), 2026)
Artificial Intelligence (AI) has emerged as a transformative technology that is reshaping traditional accounting practices and financial reporting systems. The growing complexity of financial transactions and the demand for accurate, real-time information have encouraged organizations to adopt AI-driven tools in accounting processes. This review aims to examine the impact of AI on conventional accounting practices, particularly in financial reporting, auditing, and decision-making. The study employed a systematic literature review and bibliometric analysis approach by examining peer-reviewed journal articles, conference papers, and industry publications related to AI and accounting. The findings reveal that AI significantly improves the efficiency, accuracy, and reliability of accounting operations through automation, predictive analytics, fraud detection, and real-time financial analysis. AI also enhances strategic decision-making by enabling accountants to generate data-driven insights and improve risk assessment processes. However, the study identifies several challenges, including high implementation costs, data privacy concerns, cybersecurity risks, resistance to organizational change, and the need for professionals with advanced technological competencies. The discussion highlights that while AI creates opportunities for innovation and operational effectiveness, ethical considerations and regulatory compliance remain critical issues. The study concludes that AI has the potential to fundamentally transform the accounting profession by shifting accountants’ roles from routine bookkeeping toward strategic and analytical functions. It is recommended that accounting professionals and organizations invest in continuous training, digital infrastructure, and ethical governance frameworks to maximize the benefits of AI adoption. The implications of this study emphasize the importance of integrating AI competencies into accounting education and professional practice to ensure sustainability and competitiveness in the digital era.